2009
DOI: 10.1136/jcp.2008.061960
|View full text |Cite
|
Sign up to set email alerts
|

Serrated and non-serrated polyps of the colorectum: their prevalence in an unselected case series and correlation ofBRAFmutation analysis with the diagnosis of sessile serrated adenoma

Abstract: Sessile serrated adenomas are encountered commonly in routine endoscopy practice. The histological diagnosis correlates strongly with the presence of BRAF mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 12 publications
9
106
2
4
Order By: Relevance
“…This resulted in hypermethylation and transcriptional silencing of hMLH1 in colorectal cell lines [79]. These data support the notion that mutation in BRAF is an early, tumor-initiating event and indeed has been detected in microdissected premalignant polyps or aberrant crypt foci [24][25][26][27][28][29][30][31] Similarly, mutant KRAS was described to cause DNA hypermethylation but through a different pathway that involves upregulation of ZNF304, which recruits a co-repressor complex including the DNA methyltransferase DNMT1 to the promoter of the tumor suppressor gene locus INK4_ARF and causes its transcriptional silencing [80].…”
Section: Role Of Braf In Colon Cancersupporting
confidence: 53%
See 1 more Smart Citation
“…This resulted in hypermethylation and transcriptional silencing of hMLH1 in colorectal cell lines [79]. These data support the notion that mutation in BRAF is an early, tumor-initiating event and indeed has been detected in microdissected premalignant polyps or aberrant crypt foci [24][25][26][27][28][29][30][31] Similarly, mutant KRAS was described to cause DNA hypermethylation but through a different pathway that involves upregulation of ZNF304, which recruits a co-repressor complex including the DNA methyltransferase DNMT1 to the promoter of the tumor suppressor gene locus INK4_ARF and causes its transcriptional silencing [80].…”
Section: Role Of Braf In Colon Cancersupporting
confidence: 53%
“…These mutations have already been detected when microdissected premalignant polyps or aberrant crypt foci were genotyped and revealed to be alternative events [24][25][26][27][28][29][30][31]. Mutation detection is important as it identifies tumors resistant to anti-EGFR therapy, either through receptor-blocking monoclonal antibodies or inhibitors of the receptor tyrosine kinase activity.…”
Section: Molecular and Morphological Characteristicsmentioning
confidence: 96%
“…Notably, this study also found that the female:male ratio increases as SSAs progress, as women made up 53% of those with nondysplastic SSAs, but 57%, 69%, and 76% of those with SSAs with low grade dysplasia, high grade dysplasia, and cancer respectively. A number of other studies have reported that a higher proportion of SSAs are removed from women, including Carr et al (65% female) and Spring et al (65% female) [24, 25]. It appears that there is a slight female predominance for SPs and SSAs in particular, and the sex distribution of SPs certainly differs from that of adenomas, where male sex is a clear risk factor.…”
Section: Specific Risk Factorsmentioning
confidence: 92%
“…The World Health Organization subclassifies SPs into three categories: HPs, SSAs (with or without cytological dysplasia), and TSAs (with or without conventional dysplasia) depending primarily on the crypt architecture [23]. HPs are the most prevalent of the group and make up 75%-95% of SPs, while SSAs make up less than ¼ of SPs, and TSAs are much rarer than SSAs, comprising only about 1% of SPs [24-29]. …”
Section: Overview Of the Serrated Pathway And Serrated Polyp Typesmentioning
confidence: 99%
See 1 more Smart Citation